The Implications Of Implementing eHR As A Strategic Approach In Organisation : An Exploratory Study - Chong, Eik Tze (2003)
The challenges facing management today are many: financial, technological, organisational and competition. The biggest challenge of all, that blankets all of the others, is the management of the human resource. With regulatory and legislative mandates, the dynamic nature of human resources management, the emphasis on increased productivity and reduced expenditure and expanding computer literacy, no organisations can meet these challenges without timely and accurate information. That is the reason why technology exists. This dissertation aims to highlight the usefulness of technology and how it can helps firms to overcome these challenges and achieve business success. Specifically, this dissertation explores the notion of eHR: a web-based of integrated HR related data, tools and transactions that helps organisation to acquire, develop and deploy intellectual capital at all times. This dissertation offers a clear explanation of eHR and provides an insight of the eHR applications as well as the potential benefits for organisations that embrace on such technology. As this technology is relatively new for organisations in Malaysia, we substantiate its potential benefits through some case studies of US-based organisations. The approaches of these US-based organisations will serve as evidence that eHR does indeed yield superior benefits. Drawing from that basis, we predict that the trend in eHR adoption will soon accelerate for organisations in Malaysia. To that end, overcoming barriers of implementation and an eHR implementation strategy are seen as vital for successful implementation of eHR.